The Potential Impact of Adding Ivermectin to a Mass Treatment Intervention to Reduce Malaria Transmission: A Modelling Study. (20th June 2014) - Slater, Hannah C.; Walker, Patrick G. T.; Bousema, Teun; Okell, Lucy C.; Ghani, Azra C.
Abstract : Background: Ivermectin (IVM), used alongside mass treatment strategies with an artemisinin combination therapy, has been suggested as a possible tool for reducing malaria transmission. Mosquitoes ingesting a bloodmeal containing IVM have increased mortality, reducing the probability that the parasite completes sporogony. Methods: Human pharmacokinetic data and mortality data for mosquitoes taking bloodmeals containing IVM are used to quantify the mosquitocidal effect of IVM. These are incorporated into a transmission model to estimate the impact of IVM in combination with mass treatment strategies with artemether-lumefantrine on transmission metrics. Results: Adding IVM increases the reductions in parasite prevalence achieved and delays the reemergence of parasites compared to mass treatment alone. This transmission effect is obtained through its effect on vector mortality. IVM effectiveness depends on coverage with the highest impact achieved if given to the whole population rather than only those with existing detectable parasites. Our results suggest that including IVM in a mass treatment strategy can reduce the time taken to interrupt transmission as well as help to achieve transmission interruption in transmission settings in which mass treatment strategies alone would be insufficient. Conclusions: Including IVM in mass treatment strategies could be a useful adjunct to reduce and interrupt malaria transmission.